Sustainable urban settlement and environmental challenges - Abdul Samad Hadi (Environmental Management Society, Malaysia, 2009)
The Malaysian urbanisation experiences have progressed from the grip of pseudo-urbanization in past decades before the 1970-s to the stage of mobilizing the process towards achieving the first world status by 2020 after that. The shift in development paradigms from one of development for social and spatial, rural and urban equity with expanding plantation agriculture and import substitution as the main drivers at first and the export industrialization and services later, to the sustainable development paradigm that seeks some form of balanced growth between the economic, social and the environmental pillars. Embedded in both paradigms is balanced development. The sustainable development concept is not easily applied to the city habitat for the reasons that it is the centre of modernity with economic growth as the mainstay for wealth accumulation to pay for social projects, thus leaving the environment pillar lagging behind. The article proposes city liveability instead to capture on the improved quality of city life. However, under the aegis of the two development paradigms urban centres continued to grow from largely rural to urban and international labour migration. In the last three decades, the country is witnessing the rise of extended mega urban regions focusing on the Klang valley, the Penang- Kulim industrial area and the Johor Bahru-Pasir Gudang area with minor conurbations in all states centering on the state capitals. The success in socioeconomic development in the city is not free of problems. Wealth accumulation has taken its toll on the environmental health as well as on the social situation of the country. More economic growth leads to further enlargement of cities which in turn increase more problems to both the physical and social environments. Economic vibrancy without doubt brings many benefits to the Malaysian society but the health of the environment leaves much to be desired due to unethical use of resources overt consumption. Looking to the future the society needs to be more responsible to both man and the environment